Effect of Cu, Sn and Sb addition on the structural, thermal and magnetic properties of body-centered cubic structured CoNiMnGaSi high entropy alloy - Simsek, Telem; Ozkul, Iskender; Canbay, Canan Aksu; Avar, Baris; Simsek, Tuncay; Guler, Seval Hale; Chattopadhyay, Arun K. (Springer Heidelberg, 2022)
In this study structural, morphological, thermal and magnetic properties of equiatomic CoNiMnGaSi (base), CoNiMnGaSiCu, CoNiMnGaSiSn and CoNiMnGaSiSb alloys are discussed. The formation of solid-solution nanocrystalline bcc structure of the alloys was determined by XRD and DTA techniques. SEM-EDS analyses also revealed the homogeneous distribution of the elements. The room temperature magnetic hysteresis loops showed that as-casted alloys reached saturation easily with coercivity less than or equal to 35 Oe. As the Cu and Sn were added to the alloy, the saturation magnetization was decreased from 112 emu/g to 50 emu/g, which was mainly due to the substitution of non-magnetic atoms to the magnetic Co in the base CoNiMnGaSi alloy, whereas the addition of Sb to the base alloy did not have a significant effect on the M-s. The CoNiMnGaSiSb was found to have the highest Curie Temperature of 670 K, which makes the alloy a promising candidate for power industry-related applications.
Keywords: High entropy alloys; Soft magnetic materials; Curie Temperature; Solid-solution; Magnetic properties; Arc melting